Flat-gain wide-band erbium doped fiber amplifier with hybrid gain medium - Hamida, B.A.; Azooz, S.M.; Jasim, A.A.; Eltaif, T.; Khan, S.; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier, 2016)
A new erbium-doped fiber amplifier (EDFA) is demonstrated using a combination of zirconia-based erbium-doped fiber (Zr-EDF) and silica-based Erbium-doped fiber (Si-EDF) as the gain medium. The EDFA comprises a 2 m long Zr-EDF and 9 m long Si-EDF optimized for C- and L-band operations, respectively, in a double-pass parallel configuration. A chirp fiber Bragg grating (CFBG) is used in both stages to ensure double propagation of the signal and thus to increase the attainable gain in both C- and L-band regions. At an input signal power of 0 dBm, a flat gain of 15 dB is achieved with a gain variation of less than 0.5 dB within a wide wavelength range from 1530 to 1605 nm. The corresponding noise figure varies from 6.2 to 10.8 dB within this wavelength region.